2017
DOI: 10.23937/2469-584x/1510052
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic Gastritis and Gastric Cancer Risk amongst Diabetes Mellitus Type 2 Subjects and Controls in Yaounde Cameroon Using a Panel of Serum Biomarkers (PGI, G-17)

Abstract: Introduction: Gastric inflammation is a precursor to many gastrointestinal disorders including, peptic ulcer disease, atrophic gastritis and gastric cancer. Gastritis is frequent and usually severe in patients with diabetes mellitus (DMT2), probably due to the impairment of their immune status. Atrophic gastritis is usually accompanied by low hydrochloric acid, low pepsinogens and hypergastrinemia and is the most significant risk condition for gastric cancer. Studies on atrophic gastritis are scarce amongst di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The multivariate regression analysis showed that cardiovascular disease and respiratory disease lost statistical significance in patients that were 65 years of age or older, implying that age > 65 years was a confounding factor. Diabetes mellitus is no longer significantly correlated with anemia in the presence of premalignant gastric lesions, with other studies demonstrating different results [28], [29].…”
Section: Discussionmentioning
confidence: 77%
“…The multivariate regression analysis showed that cardiovascular disease and respiratory disease lost statistical significance in patients that were 65 years of age or older, implying that age > 65 years was a confounding factor. Diabetes mellitus is no longer significantly correlated with anemia in the presence of premalignant gastric lesions, with other studies demonstrating different results [28], [29].…”
Section: Discussionmentioning
confidence: 77%
“…Patients with diabetes were found to be at higher risk for developing peptic ulcers [5]. In addition to this, a case-control study revealed that diabetic patients had a higher propensity to atrophic corpus gastritis, a significant risk factor for distal gastric cancer [6]. Therefore, the evidences raised the question whether anti-diabetic agents had protective effects against gastric diseases, especially gastric cancer.…”
Section: Introductionmentioning
confidence: 99%